Motivation for Aid Allocation and Political Ideology: A Case Study of South Korea*. (December 2015) - Sohn, Hyuk‐Sang; Yoo, Nari
Abstract : According to traditional wisdom in the foreign aid community, a donor country's official development assistance policy tends to be influenced by the political regimes' ideology. A progressive government is more likely to be humanitarian in implementing foreign aid, whereas a conservative one is apt to be more strategic and economic‐interest oriented. Given South Korea's regime change between conservatives and progressives from the Roh Tae‐woo (1988) to the Lee Myung‐bak (2012 ) administrations, this article attempts to identify shifts in South Korea's aid allocation in terms of economic, security strategic, social and humanitarian aspects. The empirical analysis of the South Korean case demonstrates that aid policies did not follow the ideological differences between governments. One of the key results is that aid allocation is more attributed to the distinct characteristics of the official development assistance management system and policies than to the party politics of South Korea.